2011
DOI: 10.1021/la200606r
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Lead(II) Ions from Aqueous Solution on Low-Temperature Exfoliated Graphene Nanosheets

Abstract: Graphene nanosheets (GNSs) that were obtained by vacuum-promoted low-temperature exfoliation were used to adsorb lead ions from an aqueous system. The pristine and thermally modified GNSs were characterized with scanning electron microscopy observation and X-ray photoelectron spectroscopy analysis. It was interestingly found that the adsorption against lead ions was enhanced by heat treatment, although the oxygen complexes of GNSs showed a significant decrease. In addition, lead ion uptake resulted in an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
200
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(205 citation statements)
references
References 30 publications
4
200
1
Order By: Relevance
“…Numerous reports described the utilization of graphene and its composites as good adsorbents for the removal of dyes and heavy metal ions from aqueous solutions (Zhao et al 2011;Cong et al 2012;Huang et al 2011;Vilela et al 2016). The applications of graphene in environment are mainly the removal of pollutants in water.…”
Section: Graphene Oxide-water Treatmentmentioning
confidence: 99%
“…Numerous reports described the utilization of graphene and its composites as good adsorbents for the removal of dyes and heavy metal ions from aqueous solutions (Zhao et al 2011;Cong et al 2012;Huang et al 2011;Vilela et al 2016). The applications of graphene in environment are mainly the removal of pollutants in water.…”
Section: Graphene Oxide-water Treatmentmentioning
confidence: 99%
“…• was observed on PVP-rGO powder, which was attributed to (002) lattice planes of the graphene [24]. The plane space d was calculated to be 0.36 nm, which was slightly larger than 0.34 nm of graphite (JCPDS No.…”
Section: Resultsmentioning
confidence: 99%
“…Graphene was considered as a good nanomaterial for removing metal ions due to its high surface area, an-tibacterial property and lower cytotoxicity [18][19][20][21][22][23][24][25][26]. In recent years, graphene nanosheets (GNSs) were fabricated by the vacuum-promoted exfoliation method at low-temperature and used to adsorb Pb ions and the adsorption capacity of about 40 mg/g was obtained [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Expanding on this topic, multiple groups have shown that GO can also be used in the adsorption Pb(II), 50,51 Cd(II), Co(II) 52 and U(VI). 53,54 It should be noted that pH plays a very important role in the adsorption of heavy metals using GO, as the pH dependent functional groups on the GO surface are the sites for metal adsorption.…”
Section: Water Remediation By Adsorptionmentioning
confidence: 99%